Static analysis of thrust bearing with lubrication hole variation in an automobile's connecting rod - Edy Suryono; Gilar Selo Yuda Pratama; Agus Jamaldi (Journal of Engineering and Applied Technology, 2023)
The research used the thrust bearing of a 1298cc automobile. The thrust-bearing material was annealed stainless steel (SS 201) with a tensile strength of 685 MPa and a yield strength of 292 MPa. The research objective was to obtain the best static thrust-bearing analysis results based on CAE software analysis. The research method included design stages, material parameters, fixed geometry determination, loading, meshing settings, computation, and result data. The simulation results were in the form of stress values, where the maximum stress value on the three-hole, one-hole, and non-hole thrust bearings were 227.2 MPa, 215.1 MPa, and 138 MPa, respectively. The non-hole thrust bearing could be the safest among all variations. The non-hole thrust bearing had a critical stress area value of 154 MPa, where it could absorb a force of 52.75% of the yield strength, the lowest strain was 8.531E-4, and had the highest minimum safety factor of 1.896.